2019
DOI: 10.1136/bmjopen-2018-023660
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre prospective cohort study of nonoperative versus operative treatment for flail chest and multiple rib fractures after blunt thoracic trauma: study protocol

Abstract: IntroductionA trend has evolved towards rib fixation for flail chest although evidence is limited. Little is known about rib fixation for multiple rib fractures without flail chest. The aim of this study is to compare rib fixation with nonoperative treatment for both patients with flail chest and patients with multiple rib fractures.Methods and analysisIn this study protocol for a multicentre prospective cohort study, all patients with three or more rib fractures admitted to one of the five participating centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…A detailed description of the methods and surgical procedures used in this study is available in the published study protocol [ 9 ]. Here, we focus on patients with multiple rib fractures; the results of patients with a flail chest (paradoxical movement of a portion of the chest wall) will be addressed in a separate study.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the methods and surgical procedures used in this study is available in the published study protocol [ 9 ]. Here, we focus on patients with multiple rib fractures; the results of patients with a flail chest (paradoxical movement of a portion of the chest wall) will be addressed in a separate study.…”
Section: Methodsmentioning
confidence: 99%
“…An example of a study of a type 3 comparisons is the Opvent study, which is a multicenter prospective cohort study, including patients with three or more rib fractures admitted to one of the five participating centers [ 32 ]. In two centers, rib fixation is the standard-of-care for flail chest or multiple rib fractures, while in three other centers nonoperative treatment is.…”
Section: Different Research Questions In Surgical Intervention Studiementioning
confidence: 99%
“…However, the comparison of operated patients with a historic patient cohort from the very same center obviates a selection bias that is present in any other study design except prospective randomized controlled clinical trials. The latter are hardly realizable in the acute trauma setting [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technically, surgical stabilization of rib fractures (SSRF) goes along with supplementary soft tissue trauma to the injured chest wall and may additionally impair respiratory mechanics by muscle injury. As a result, no clear-cut selection criteria exist so far what patients benefit from SSRF [10][11][12][13][14][15]. Numerous studies have shown that early SSRF within the first week after chest trauma is effective to prevent secondary lung injury and to improve patient recovery [10,12,13].…”
Section: Introductionmentioning
confidence: 99%